Oversight on the borderline: Quality improvement and pragmatic research. (October 2015) - Finkelstein, Jonathan A; Brickman, Andrew L; Capron, Alexander; Ford, Daniel E; Gombosev, Adrijana; Greene, Sarah M; Iafrate, R Peter; Kolaczkowski, Laura; Pallin, Sarah C; Pletcher, Mark J; Staman, Karen L; Vazquez, Miguel A; et al.
Pragmatic research that compares interventions to improve the organization and delivery of health care may overlap, in both goals and methods, with quality improvement activities. When activities have attributes of both research and quality improvement, confusion often arises about what ethical oversight is, or should be, required. For routine quality improvement, in which the delivery of health care is modified in minor ways that create only minimal risks, oversight by local clinical or administrative leaders utilizing institutional policies may be sufficient. However, additional consideration should be given to activities that go beyond routine, local quality improvement to first determine whether such non-routine activities constitute research or quality improvement and, in either case, to ensure that independent oversight will occur. This should promote rigor, transparency, and protection of patients' and clinicians' rights, well-being, and privacy in all such activities. Specifically, we recommend that (1) health care organizations should have systematic policies and processes for designating activities as routine quality improvement, non-routine quality improvement, or quality improvement research and determining what oversight each will receive. (2) Health care organizations should have formal and explicit oversight processes for non-routine quality improvement activities that may include input from institutional quality improvement experts, health services researchers, administrators, clinicians, patient representatives, and those experienced in the ethics review of health care activities. (3) Quality improvement research requires review by an institutional review board; for such review to be effective, institutional review boards should develop particular expertise in assessing quality improvement research. (4) Stakeholders should be included in the review of non-routine quality improvement and quality improvement–related research proposals. Only by doing so will we optimally leverage both pragmatic research on health care delivery and local implementation through quality improvement as complementary activities for improving health.